Pengaruh Molases Pada Amoniasi Jerami Padi Menggunakan Urea Terhadap Kecernaan Bahan Kering dan Bahan Organik In Vitro - Muhamad Bata (Jurnal Agripet, 2008)
The effect of molasses on ammoniated straw by using urea on dry and organic matter digestibility as in vitroABSTRACT. Aimed of this research was to find out the optimal level of molasses addition to improve quality, dry matter and organic matter digestibility of rice straw ammonization process. Materials used were rumen fluid of fistula cattle, grind of rice straw, water, urea and molasses. Research designed used Completely Randomized Design (CRD). As treatments were R0: rice straw 1000 g dry matter + 500 g water + 50 g urea + 0 percent of molasses, R1: R0 + 15 percent of molasses, R2: R0 + 30 percent of molasses. Urea and molasses dissolved in water and then entered into pollybag. All pollybag observe and let for 15 days, each treatment replicated 6 times. Variable measured were dry matter digestibility and organic matter digestibility. Research result showed that ammonization product of NH3, Acidity Level and crude fiber having decreased while crude protein content increased. Variance analysis indicated that treatments had significant effect (P0.05) on dry matter and organic matter digestibility. Orthogonal polynomial test indicated that level of molasses increase (P0.05) of dry matter and organic matter digestibility linearly. It can be concluded that addition up to 30 percent in ammoniating of rice straw using urea can improve quality of ammonization and increasing dry matter and organic matter digestibility.